A self-repairing modified bio-based coating material with super strong mechanical properties and preparation method thereof

By introducing toughening agents and self-healing materials into bio-based coated controlled-release fertilizers, a dynamic network is formed, which solves the problems of low density and difficulty in self-healing of bio-based coated controlled-release fertilizer membranes, and achieves high mechanical strength and Stable controlled release performance.

CN117886645BActive Publication Date: 2025-01-24SHANDONG AGRICULTURAL UNIVERSITY

Patent Information

Application Number
CN202410072745.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2025-01-24
Estimated Expiration
2044-01-18

AI Technical Summary

Technical Problem

The existing bio-based polyurethane envelope controlled release fertilizer has low membrane density, poor controlled release quality, and is difficult to achieve self-repair, which limits its industrial development.

Method used

Bio-based coating materials modified with super mechanical properties and self-healing are used. By introducing toughening agents and self-healing materials into the coating liquid matrix, a dynamic network loaded with multiple complex ions is formed to achieve covalent bonding and multiple complexation. Double cross-linking of molecules promotes rapid repair of damaged areas.

Benefits of technology

It improves the mechanical strength and controlled release performance of bio-based coated controlled-release fertilizers, realizes self-repair of the membrane shell, prevents large-scale release of nutrients, and maintains the stability of nutrient release.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117886645B_ABST
    Figure CN117886645B_ABST
Patent Text Reader

Abstract

The present invention discloses a bio-based coating material with super mechanical properties and self-repairing modification and a preparation method thereof, and belongs to the technical field of controlled release fertilizer production. The bio-based coating material of the present invention is made of the following raw materials in parts by weight: 100-120 parts of coating liquid matrix, 0.5-1 parts of toughening agent, and 5-10 parts of self-repairing material. The present invention uses livestock farm waste as the raw material for making coated controlled release fertilizer membrane shell, which reduces costs and promotes the recycling and reuse of waste. By introducing metal ions into the covalent network, the stability of the network and the mobility of covalent bonds and hydrogen bonds are improved, the metal ions and the toughening agent undergo complexation reaction, and the presence of multiple complex molecules promotes the dissipation of energy when the covalent bonds are broken and reorganized, giving the coating super mechanical properties and the ability to continuously self-repair damaged areas at room temperature, effectively solving the problem of poor elasticity and easy damage of the membrane shell of the bio-based slow-release fertilizer, which is of great significance for improving the quality and utilization rate of slow-release fertilizers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of controlled-release fertilizer production, and in particular to a self-repairing modified bio-based coating material with super mechanical properties and a preparation method thereof. Background Art

[0002] Bio-based polyurethane has shown broad application prospects in the preparation of fertilizer controlled-release membranes due to its low raw material price, renewable resources, and environmental friendliness. However, due to the complex composition of biological raw materials and the presence of some impurities that do not participate in the reaction, the prepared bio-based controlled-release membranes have low density and poor controlled-release quality. At the same time, during the nutrient release process, along with the entry of water and the dissolution of nutrients from the membrane shell, these non-film-forming substances may dissolve out of the membrane along with the solution, resulting in increased pores or damage in the membrane, which leads to rapid nutrient release and affects the controlled-release quality (Ma et al., 2018). Most of the existing modification methods cannot repair the damaged structure of the membrane, which is also a bottleneck problem restricting the industrial development of bio-based polyurethane coated controlled-release fertilizers. Therefore, giving the membrane a self-repairing function and realizing the spontaneous repair of micropores or damage in the bio-based membrane is the key to solving this type of problem.

[0003] At present, there are few studies on self-healing bio-based polyurethane controlled-release membranes, and there is a lack of unified understanding of the self-healing mode of action. Tian et al. (2022) prepared bio-based polyurethane from wood cellulose and castor oil. By cross-linking with a polymer containing dynamic disulfide bonds, the membrane can spontaneously repair micropores during the coating process, but the self-healing function disappears immediately after the membrane is cured; once the coated fertilizer is damaged by the dissolution of insoluble substances during the nutrient release process, the nutrient release will be accelerated, affecting the controlled release quality. Patent CN113788711A discloses a self-healing bio-based membrane, coated controlled-release fertilizer and preparation method. A polyurethane film that can self-heal at room temperature is prepared by reacting liquefied polyols and modified isocyanates. The principle is to graft reversible covalent bonds into the covalent network to give it a self-healing function. This preparation method can repair pores and cracks formed by the dissolution of non-film-forming substances to ensure the integrity of the coating, but the repair performance is related to the migration and reorganization of chemical bonds. The mobility of the grafted chemical bonds deteriorates, which is not conducive to continuous repair.

[0004] Therefore, new self-repair technologies still need to be developed to regulate the nutrient release characteristics of coated controlled-release fertilizers, and to provide theoretical and technical support for the development of a new generation of green, efficient, and low-cost bio-based polyurethane coated controlled-release fertilizers. Summary of the invention

[0005] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is a self-repairing modified bio-based coating material with super mechanical properties and a preparation method thereof. The bio-based coating material of the present invention has excellent self-repairing properties and super mechanical properties, solves the problem of easy damage and breakage of the membrane shell in the promotion and application of existing bio-based coated controlled-release fertilizers, and improves the nutrient release performance of bio-based coated controlled-release fertilizers.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] The first aspect of the present invention provides a bio-based coating material with super mechanical properties and self-repairing modification, comprising the following raw materials in parts by weight:

[0008] 100-120 parts of coating liquid matrix, 0.5-1 parts of toughening agent, 5-10 parts of self-healing material;

[0009] The toughening agent is obtained by reacting 4-hydroxynonenal, maleimide and p-cresol in a volume ratio of 50:(30-40):(5-10);

[0010] The self-healing material is obtained by reacting a first component and a second component in a molar ratio of 1:(0.05-0.1); the first component is one or more of allyl disulfide, dibenzyl diselenide and neopentyl glycol diborate; the second component is one or more of anhydrous magnesium chloride, anhydrous ferric chloride and anhydrous zinc chloride.

[0011] Preferably, the coating liquid matrix is ​​a bio-based polyurethane obtained by reacting liquefied polyol and isocyanate.

[0012] More preferably, the liquefied polyol is obtained by reacting component A, polyethylene glycol 800, glycerol and ammonium sulfate in a mass ratio of (20-40):90:10:(3-5); the component A is selected from one or more of chicken feathers, egg shells and chicken manure.

[0013] More preferably, the isocyanate is selected from one or more of hexamethylene diisocyanate, 3-(trifluoromethyl)phenyl isocyanate, and 5-isocyanate-2-methylpyridine.

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned bio-based coating material with super mechanical properties and self-repairing modification, comprising the following steps:

[0015] (1) adding maleimide to 4-hydroxynonenal, stirring continuously at 55-65° C. for 20-40 min, adding p-cresol after the stirring is completed, adjusting the pH to 10 after the reaction is stable, and obtaining a toughening agent after drying;

[0016] (2) dissolving the second component in anhydrous ethanol, adding the first component, stirring continuously at 30-40° C., adjusting the pH to 9.5-10, stirring for 5-10 minutes, and then ultrasonically oscillating, and drying to obtain a self-healing material;

[0017] (3) Add the toughening agent to the self-healing material, continue stirring under the condition of passing nitrogen, mix the two evenly, then adjust the pH to 10, and after drying, obtain an intermediate product; add the intermediate product to the coating liquid matrix, add an organic solvent to the mixture, stir for 3-5 minutes, ultrasonically vibrate for 15-25 minutes, take out after it is uniform, stir to remove excess organic solvent, and stop stirring when it becomes viscous, thereby obtaining a self-healing modified bio-based coating material with super mechanical properties.

[0018] Preferably, in step (3), the organic solvent is tetrahydrofuran.

[0019] The third aspect of the present invention provides the use of the above-mentioned self-repairing modified bio-based coating material with super mechanical properties in the preparation of controlled-release fertilizers.

[0020] The fourth aspect of the present invention provides a self-healing coated controlled-release fertilizer, comprising a fertilizer core, and a bio-based coating material with super strong mechanical properties and self-healing modification sprayed on the surface of the fertilizer core; the bio-based coating material with super strong mechanical properties and self-healing modification accounts for 5-7% of the weight of the fertilizer core.

[0021] A fifth aspect of the present invention provides a method for preparing the self-repairing coated controlled-release fertilizer, comprising the following steps:

[0022] The self-repairing modified bio-based coating material with super mechanical properties is sprayed evenly on the surface of the preheated fertilizer core at a pressure of 0.3-0.5MPa, and cured at 65-75°C for 4-6 minutes.

[0023] Beneficial effects of the present invention:

[0024] (1) The present invention uses liquefied waste as a raw material for synthesizing the coating material, thereby realizing the recycling and reuse of the waste and reducing the production cost.

[0025] (2) The present invention solves the problem of poor elasticity and low strength of the fertilizer film shell, improves the mechanical strength of the fertilizer film shell, and improves the quality of the fertilizer.

[0026] (3) The present invention solves the problem of rapid nutrient release after fertilizer damage. When the membrane shell is damaged due to external factors, it can spontaneously repair the damaged area at 25-75°C, preventing a large amount of nutrients from being released, thereby maintaining the stability of nutrient release. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1: Fourier infrared spectroscopy test results of the self-repairing modified bio-based coating materials with super strong mechanical properties prepared in Examples 1-3 of the present invention.

[0028] Figure 2 : The membrane shell formed after curing of the self-repairing modified bio-based coating material with super mechanical properties prepared in Example 1 of the present invention is tested by in-situ infrared spectroscopy to see whether it has thermal reversibility.

[0029] Figure 3 : The stress-strain curve measurement results of the membrane shell formed after the curing of the self-repairing modified bio-based coating material with super strong mechanical properties prepared in Examples 1-3 of the present invention.

[0030] Figure 4 : Photos of the self-repairing modified bio-based coating material with super strong mechanical properties synthesized in Example 1 before and after repair.

[0031] Figure 5 : Preparation of Example 4 of the present invention: Bio-based coated controlled-release fertilizer The surface and cross-section of the bio-based polyurethane film shell were observed under a scanning electron microscope (SEM).

[0032] Figure 6 : Test results of water absorption and swelling properties of the coated controlled-release fertilizers prepared in Example 4 and Comparative Example 1 of the present invention.

[0033] Figure 7 : Nutrient release curve of coated controlled-release fertilizer after membrane shell damage repair in Example 4 of the present invention.

[0034] Figure 8 : The strength test results of the surface membrane shell of the coated controlled-release fertilizer prepared in Examples 4-6 of the present invention.

[0035] Fig. 9 : Nutrient release curves of the coated controlled-release fertilizers prepared in Examples 4-6 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0036] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0037] As mentioned above, existing bio-based coated controlled-release fertilizers have been prepared using raw materials such as liquefied lignin, waste oil, and liquefied poplar fluff, which are affordable, widely available, and have certain environmental benefits. However, the controlled-release fertilizer films prepared using these materials still have defects such as poor elasticity, low strength, and easy breakage, which restricts the promotion and application of bio-based coated controlled-release fertilizers.

[0038] In view of this, the present invention has developed a bio-based coating material with super mechanical properties and self-repairing modification. The bio-based coating material with super mechanical properties and self-repairing modification of the present invention is made by reacting a coating liquid matrix, a toughening agent, and a self-repairing material. By constructing a layer of dynamic network loaded with multiple complex ions on the fertilizer surface, double cross-linking between covalent bonds and multiple complex molecules is achieved. Their breakage and recombination promote the rapid repair of the damaged area and the dissipation of the material surface energy, and can withstand external forces with greater energy. The stability of fertilizer nutrient release is guaranteed, and the phenomenon of rapid nutrient release caused by membrane shell damage in existing bio-based coated controlled-release fertilizers is solved.

[0039] In one embodiment of the present invention, a method for preparing a bio-based coating material with super mechanical properties and self-repairing modification is provided, as follows:

[0040] The toughening agent is added into the self-healing material, and the mixture is continuously stirred under nitrogen flow to mix the two materials evenly. The pH value is then adjusted to 10, and the mixture is dried to obtain an intermediate product.

[0041] The intermediate product is added into the coating liquid matrix, and 10-20 ml of organic solvent is added into the mixture. After stirring for 3-5 minutes, the mixture is shaken for 20 minutes using an ultrasonic oscillator. After the mixture is uniform, it is taken out and stirred slowly and evenly using a glass rod to remove excess organic solvent. When the mixture becomes viscous, stirring is stopped to obtain a self-healing modified bio-based coating material with super mechanical properties.

[0042] The coating material of the present invention has excellent mechanical properties, continuous self-repairing properties and excellent controlled release properties. The mechanism of action of the coating material of the present invention is:

[0043] The second component of the self-healing material can be dissolved in anhydrous ethanol. After the first component is added, the free metal ions will be adsorbed on the covalent bonds of the first component, and the added toughening agent will undergo complexation reaction with the metal ions loaded on the covalent bonds to form multiple complex molecules, which will finally react with the coating liquid matrix to form a dynamic network loaded with multiple complex ions. There are double dynamic crosslinks in the network, which have a stronger effect than a single dynamic crosslink, can better promote energy dissipation, and increase the migration rate of molecules, thereby improving the repair efficiency and mechanical properties.

[0044] In summary, the current bio-based coated controlled-release fertilizers have the problems of poor toughness, low elasticity, and the membrane shell being easily damaged by external influences. The present invention originally introduces self-healing materials and toughening agents into the coating liquid of controlled-release fertilizers, wherein the toughening agent can react with metal ions loaded on covalent bonds to form a dynamic crosslink, which can synergize with covalent bonds to form a closely connected double dynamic crosslink; the self-healing material provides covalent bonds (disulfide bonds, diselenide bonds, boron ester bonds) and loaded metal ions (iron ions, magnesium ions, zinc ions). In the process of bio-based polyurethane film formation, the self-healing material and the toughening agent work together, and the two are intertwined to form a tight double dynamic crosslink. Introducing this double dynamic crosslink into the polyurethane network can give the polyurethane film excellent self-healing properties and strong mechanical properties.

[0045] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0046] The test materials used in the examples and comparative examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels. Among them: the CAS number of allyl disulfide is: 27817-67-0; the CAS number of neopentyl glycol diborate is: 201733-56-4; the CAS number of 3-(trifluoromethyl)phenyl isocyanate is: 329-01-1.

[0047] The chicken feathers and chicken manure used are conventional chicken farm waste.

[0048] Example 1: Preparation of self-repairing modified bio-based coating material with super strong mechanical properties

[0049] (1) Preparation of coating fluid matrix:

[0050] Add 270g of polyethylene glycol 800, 30g of glycerol and 9g of concentrated sulfuric acid into a three-necked flask and continue stirring for 1h. Heat it to 150°C, then add 60g of chicken feathers into the three-necked flask and continue stirring. After it is completely decomposed into black liquid, take it out and cool it to obtain liquefied polyol.

[0051] After mixing 60 g of the liquefied polyol prepared above with 90 g of hexamethylene diisocyanate, stirring was continued until the mixture was uniformly mixed, 1 drop of dibutyltin dilaurate was added, stirring was continued for 1 min to prepare a coating liquid matrix, and then the mixture was transferred to a 50° C. vacuum drying oven for storage.

[0052] (2) Preparation of self-healing materials:

[0053] Dissolve 0.5 g of anhydrous ferric chloride in 10 ml of anhydrous ethanol, then add 9.02 g of diallyl disulfide to the ferric chloride solution, continue stirring evenly at 30°C, adjust the pH to 10, continue stirring for 5 minutes, then place it in an ultrasonic oscillator for 1 hour, and finally take it out and dry it to obtain a self-healing material.

[0054] (3) Preparation of toughening agent:

[0055] 40 ml of maleimide was added to 50 ml of 4-hydroxynonenal, and the mixture was placed in a magnetic stirrer and stirred continuously at 55° C. for 30 min. After the stirring was completed, 10 ml of p-cresol was added. After the reaction was stable (the criterion for determining the stability of the reaction was that no bubbles were generated), the pH was adjusted to 10, and the toughening agent was obtained after drying.

[0056] (4) Preparation of bio-based coating materials:

[0057] 0.25 g of the toughening agent synthesized in step (3) was added to 2.5 g of the self-healing material synthesized in step (2), and the mixture was stirred continuously under nitrogen gas flow to mix the two evenly. The pH was then adjusted to 10, and the mixture was dried to obtain an intermediate product.

[0058] The intermediate product was added into 50 g of the coating liquid matrix synthesized in step (1), and 20 ml of tetrahydrofuran was added to the mixture. After stirring for 5 minutes, the mixture was shaken for 20 minutes using an ultrasonic oscillator. The mixture was taken out and stirred slowly and evenly using a glass rod to remove excess organic solvent. When the mixture became viscous, stirring was stopped to obtain a self-healing modified bio-based coating material with super mechanical properties.

[0059] Example 2: Preparation of self-repairing modified bio-based coating material with super strong mechanical properties

[0060] (1) Preparation of coating fluid matrix:

[0061] Add 270g of polyethylene glycol 800, 30g of glycerol and 12g of concentrated sulfuric acid into a three-necked flask and continue stirring for 1h. Heat it to 150°C, then add 90g of chicken feathers into the three-necked flask and continue stirring. After it is completely decomposed into black liquid, take it out and cool it to obtain liquefied polyol.

[0062] After mixing 60 g of the liquefied polyol prepared above with 180 g of 3-(trifluoromethyl)phenyl isocyanate, stirring was continued until the mixture was uniformly mixed, 1 drop of dibutyltin dilaurate was added, stirring was continued for 1 min to prepare a coating liquid matrix, and then the mixture was transferred to a 50° C. vacuum drying oven for storage.

[0063] (2) Preparation of self-healing materials:

[0064] Dissolve 0.5 g of anhydrous magnesium chloride in 20 ml of anhydrous ethanol, then add 17.91 g of dibenzyl diselenide to the magnesium chloride solution, continue stirring evenly at 35°C, adjust the pH to 10, continue stirring for 7 minutes, then place in an ultrasonic oscillator for 1 hour, and finally take out and dry to obtain a self-healing material.

[0065] (3) Preparation of toughening agent:

[0066] 35 ml of maleimide was added into 50 ml of 4-hydroxynonenal, and the mixture was placed in a magnetic stirrer and stirred continuously at 60° C. for 30 min. After the stirring was completed, 7 ml of p-cresol was added. After the reaction was stable (the criterion for determining the stability of the reaction was that no bubbles were generated), the pH was adjusted to 10, and the toughening agent was obtained after drying.

[0067] (4) Preparation of bio-based coating materials:

[0068] 0.5 g of the toughening agent synthesized in step (3) was added to 3.5 g of the self-healing material synthesized in step (2), and the mixture was stirred continuously under nitrogen gas flow to mix the two evenly. The pH was then adjusted to 10, and the mixture was dried to obtain an intermediate product.

[0069] The intermediate product was added to 55 g of the coating liquid matrix synthesized in step (1), and 20 ml of tetrahydrofuran was added to the mixture. After stirring for 5 minutes, the mixture was shaken for 20 minutes using an ultrasonic oscillator. The mixture was taken out and stirred slowly and evenly using a glass rod to remove excess organic solvent. When the mixture became viscous, stirring was stopped to obtain a self-healing modified bio-based coating material with super mechanical properties.

[0070] Example 3: Preparation of self-repairing modified bio-based coating material with super strong mechanical properties

[0071] (1) Preparation of coating fluid matrix:

[0072] Add 270g of polyethylene glycol 800, 30g of glycerol and 15g of concentrated sulfuric acid into a three-necked flask and continue stirring for 1h. Heat it to 150°C, then add 120g of chicken manure into the three-necked flask and continue stirring. After it is completely decomposed into black liquid, take it out and cool it to obtain liquefied polyol.

[0073] After mixing 60 g of the liquefied polyol prepared above with 180 g of 5-isocyanate-2-methylpyridine, stirring was continued until the mixture was uniformly mixed, 1 drop of dibutyltin dilaurate was added, stirring was continued for 1 min to prepare a coating liquid matrix, and then the mixture was transferred to a 50° C. vacuum drying oven for storage.

[0074] (2) Preparation of self-healing materials:

[0075] Dissolve 0.5 g of anhydrous zinc chloride in 20 ml of anhydrous ethanol, then add 12.45 g of neopentyl glycol diborate to the zinc chloride solution, continue stirring evenly at 40°C, adjust the pH to 10, continue stirring for 10 minutes, then place in an ultrasonic oscillator for 1 hour, and finally take out and dry to obtain a self-healing material.

[0076] (3) Preparation of toughening agent:

[0077] 30 ml of maleimide was added into 50 ml of 4-hydroxynonenal, and the mixture was placed in a magnetic stirrer and stirred continuously at 65° C. for 30 min. After the stirring was completed, 5 ml of p-cresol was added. After the reaction was stable (the criterion for determining the stability of the reaction was that no bubbles were generated), the pH was adjusted to 10, and the toughening agent was obtained after drying.

[0078] (4) Preparation of bio-based coating materials:

[0079] 0.5 g of the toughening agent synthesized in step (3) was added to 5 g of the self-healing material synthesized in step (2), and the mixture was stirred continuously under nitrogen gas flow to mix the two evenly. The pH was then adjusted to 10, and the mixture was dried to obtain an intermediate product.

[0080] The intermediate product was added to 60 g of the coating liquid matrix synthesized in step (1), and 20 ml of tetrahydrofuran was added to the mixture. After stirring for 5 minutes, the mixture was shaken for 20 minutes using an ultrasonic oscillator. The mixture was taken out and stirred slowly and evenly using a glass rod to remove excess organic solvent. When the mixture became viscous, stirring was stopped to obtain a self-healing modified bio-based coating material with super mechanical properties.

[0081] Example 4: Preparation of self-repairing coated controlled-release fertilizer

[0082] Take 1500g of polished urea and place it in a drum coating machine, set the speed to 20rps, preheat at 70°C for 30min, and then use a spray gun to spray the self-repairing modified bio-based coating material with super mechanical properties prepared in Example 1 onto the urea particles rotating in the drum coating machine. Curing for 5min, each spraying amount accounts for 0.5% of the fertilizer core, repeat the spraying until the mass of the bio-based coating material accounts for 5% of the mass of the fertilizer core, and prepare a self-repairing bio-based coated controlled-release fertilizer.

[0083] Example 5: Preparation of self-repairing coated controlled-release fertilizer

[0084] Take 1500g of polished urea and place it in a drum coating machine, set the speed to 20rps, preheat at 70°C for 30min, and then use a spray gun to spray the self-repairing modified bio-based coating material with super mechanical properties prepared in Example 2 onto the urea particles rotating in the drum coating machine. Curing for 5min, each spraying amount accounts for 0.5% of the fertilizer core, and repeat the spraying until the mass of the bio-based coating material accounts for 7% of the mass of the fertilizer core, to prepare a self-repairing bio-based coated controlled-release fertilizer.

[0085] Example 6: Preparation of self-repairing coated controlled-release fertilizer

[0086] Take 1500g of polished urea and place it in a drum coating machine, set the speed to 20rps, preheat at 70°C for 30min, and then use a spray gun to spray the self-repairing modified bio-based coating material with super mechanical properties prepared in Example 3 onto the urea particles rotating in the drum coating machine. Curing for 5min, each spraying amount accounts for 0.5% of the fertilizer core, and repeat the spraying until the mass of the bio-based coating material accounts for 6% of the mass of the fertilizer core, to prepare a self-repairing bio-based coated controlled-release fertilizer.

[0087] Comparative Example 1: (Only using coating liquid matrix for coating)

[0088] The preparation method of the coating liquid matrix is ​​the same as that in Example 1.

[0089] Take 1500g of polished urea and place it in a drum coating machine, set the speed to 20rps, preheat at 70℃ for 30min, then use a spray gun to spray the coating liquid matrix onto the urea particles rotating in the drum coating machine, and solidify for 10min. The amount of each spraying accounts for 0.5% of the fertilizer core. Repeat the spraying until the mass of the coating liquid matrix accounts for 5% of the mass of the fertilizer core to prepare a coated controlled-release fertilizer.

[0090] Comparative Example 2: (Encapsulation using "encapsulation liquid matrix + self-healing material")

[0091] The preparation method of the coating liquid matrix and the self-healing material is the same as that in Example 1.

[0092] Add 2.5 g of self-healing material into 50 g of coating liquid matrix, add 20 ml of tetrahydrofuran to the mixture, stir for 5 minutes, and then shake it with an ultrasonic oscillator for 20 minutes. After the mixture is evenly mixed, take it out and stir it slowly and evenly with a glass rod to remove excess organic solvent. Stop stirring when the mixture becomes viscous to obtain a bio-based coating material.

[0093] Take 1500g of polished urea and place it in a drum coating machine, set the speed to 20rps, preheat at 70℃ for 30min, then use a spray gun to spray the bio-based coating material onto the urea particles rotating in the drum coating machine and cure for 5min. The amount of each spraying accounts for 0.5% of the fertilizer core. Repeat the spraying until the mass of the bio-based coating material accounts for 5% of the mass of the fertilizer core to prepare a coated controlled-release fertilizer.

[0094] Comparative Example 3: (Using "coating liquid matrix + toughening agent" for coating)

[0095] The preparation method of the coating liquid matrix and the toughening agent is the same as that of Example 1.

[0096] 0.25 g of toughening agent was added into 50 g of coating liquid matrix, and 20 ml of tetrahydrofuran was added into the mixture. After stirring for 5 min, the mixture was shaken for 20 min using an ultrasonic shaker. After being evenly mixed, the mixture was taken out and stirred slowly and evenly using a glass rod to remove excess organic solvent. When the mixture became viscous, stirring was stopped to obtain a bio-based coating material.

[0097] Take 1500g of polished urea and place it in a drum coating machine, set the speed to 20rps, preheat at 70℃ for 30min, then use a spray gun to spray the bio-based coating material onto the urea particles rotating in the drum coating machine and cure for 5min. The amount of each spraying accounts for 0.5% of the fertilizer core. Repeat the spraying until the mass of the bio-based coating material accounts for 5% of the mass of the fertilizer core to prepare a coated controlled-release fertilizer.

[0098] Test Example 1: Performance testing of bio-based coating materials with self-repairing modification and super strong mechanical properties

[0099] The bio-based coating material with super mechanical properties and self-repairing modification synthesized in Examples 1-3 was cut after curing into a film, and the changes of characteristic groups in the material were tested by Fourier infrared spectrometer. Figure 1 It can be seen that the samples synthesized in Examples 1-3 all exhibit similar structures, with -1 The characteristic peak of the generated NH bond was found at 1597cm -1 The C=O bond characteristic peaks were found at 2280. The appearance of these two characteristic peaks proves the formation of polyurethane coating. -1 The characteristic peak of -NCO bond disappears, indicating that the isocyanate has been completely reacted.

[0100] The thermal properties of the self-repairing modified bio-based coating material with super mechanical properties synthesized in Example 1 were tested using an in-situ infrared spectrometer, and the test temperatures were 25, 40, 55, 70, 85, and 100°C, respectively. Figure 2As shown, the infrared peaks at 25 and 40°C did not move, but when the temperature rose to 55°C, the infrared peaks shifted. The results show that the bio-based coating material prepared by the present invention has thermal reversibility, and thermal reversibility indicates that the migration of molecular bonds is active, which is conducive to the self-repair process.

[0101] The stress-strain curves of the self-repairing modified bio-based coating materials with super mechanical properties synthesized in Examples 1-3 were tested using a universal testing machine. Figure 3 As shown, the elongation rates of Examples 1-3 are all above 700%, and the elongation rate of Example 1 is even above 1200%, which has excellent elongation performance.

[0102] The bio-based coating material has excellent tensile properties, which can make the prepared coated fertilizer have sufficient toughness after absorbing water and swelling, preventing the film material from swelling and cracking due to water absorption, thereby extending the nutrient release period of the fertilizer.

[0103] The self-repairing modified bio-based coating material with super mechanical properties synthesized in Example 1 was cured into a film, the film was cut and damaged, and then placed in a 25°C environment for self-repair for 24 hours.

[0104] Photos before and after restoration Figure 4 As shown, the results show that the bio-based coating material prepared by the present invention has excellent self-healing properties.

[0105] Test Example 2: Performance test of bio-based coated controlled-release fertilizer prepared using the coating material of the present invention

[0106] 1. Bio-based coated controlled-release fertilizer membrane shell morphology:

[0107] The treated membrane shell of the bio-based coated controlled-release fertilizer prepared in Example 4 was placed under a scanning electron microscope (SEM) for observation. Figure 5 As shown, the membrane shell of the bio-based coated controlled-release fertilizer prepared by the present invention is flat and dense.

[0108] 2. Water absorption and expansion performance test:

[0109] The coated controlled-release fertilizers prepared in Example 4 and Comparative Example 1 were placed in water to examine the changes in the membrane shell after water absorption and expansion. Figure 6 As shown, after the bio-based coated controlled-release fertilizer prepared in Example 4 absorbed water and swelled, its membrane shell had excellent elasticity and did not rupture; while after the bio-based coated controlled-release fertilizer prepared in Comparative Example 1 absorbed water and swelled, the membrane shell ruptured.

[0110] 3. Test of self-healing performance

[0111] The coated controlled-release fertilizer prepared in Example 4-6 was cut with a force of 2N. After the cutting was completed, it was placed in a 25°C environment for self-repair for 10 minutes, 24 hours, and 48 hours respectively. The repaired fertilizer in Example 4-6 was placed in water to test its nitrogen release rate. Figure 7 As shown, in the treatment group with 10 min of repair, the initial release rates of Examples 4-6 were 38.93%, 22.50%, and 37.63%, respectively. Figure 7 A); in the treatment group after 24h repair, the initial release rates of Examples 4-6 were 6.97%, 6.18%, and 9.47%, respectively ( Figure 7 B); The initial release rates of the treatment groups after 48 hours of repair were 4.95%, 3.15%, and 3.95% ( Figure 7 C). It can be clearly seen that the longer the repair time, the better the repair effect. The repair efficiency after 48 hours of final repair (repair efficiency refers to the ratio of the release cycle after repair to the release cycle when not damaged) was 65.51%, 73.23% and 65.71% respectively.

[0112] 4. Test of membrane shell strength

[0113] 100g of the coated controlled-release fertilizer prepared in Examples 4-6 and Comparative Example 1 were weighed and placed in transparent plastic bottles. Eight small steel balls with a diameter of 2.5cm were placed in each bottle. The bottles were placed in a shaker at a speed of 200 rap / min. Samples were taken at 20, 40, 60, and 80 minutes, and then immediately placed in water. The initial release rate of N was measured after 24 hours. The results are shown in Figure 2. Figure 8 As shown, the coated controlled-release fertilizer prepared in Comparative Example 1 was damaged after the collision, which is the reason why the initial nutrient release rate gradually increased at the four time intervals of the collision. However, the nutrient release of the coated controlled-release fertilizer prepared in Examples 4-6 of the present invention was still maintained within a stable range, proving that the rigidity of the fertilizer surface membrane shell is relatively strong.

[0114] 5. Nutrient release determination

[0115] The nitrogen release rates of the coated controlled-release fertilizers prepared in Examples 4 to 6 and Comparative Examples 1 to 3 were determined according to the National Standard for Slow-Release Fertilizers GB / T 23348-2009 of the People's Republic of China.

[0116] The results are as follows Fig. 9 As shown, the release period of the bio-based coated fertilizer in Example 4 is 58 days; the release period of the bio-based coated fertilizer in Example 5 is 71 days; the release period of the bio-based coated fertilizer in Example 6 is 70 days; the release period of the bio-based coated fertilizer in Comparative Example 1 is 40 days; the release period of the bio-based coated fertilizer in Comparative Example 2 is 47 days; and the release period of the bio-based coated fertilizer in Comparative Example 3 is 40 days.

[0117] The results show that the bio-based coated fertilizer prepared by the present invention can significantly prolong the nutrient release time.

[0118] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A self-repairing modified bio-based coating material with super mechanical properties, characterized in that: The invention comprises the following raw materials in parts by weight: 100-120 parts of coating liquid matrix, 0.5-1 parts of toughening agent, 5-10 parts of self-healing material; The toughening agent is obtained by reacting 4-hydroxynonenal, maleimide and p-cresol in a volume ratio of 50:(30-40):(5-10); The self-healing material is obtained by reacting a first component and a second component in a molar ratio of 1:(0.05-0.1); the first component is one or more of allyl disulfide, dibenzyl diselenide and neopentyl glycol diborate; the second component is one or more of anhydrous magnesium chloride, anhydrous ferric chloride and anhydrous zinc chloride; The coating liquid matrix is ​​a bio-based polyurethane obtained by reacting a liquefied polyol and an isocyanate; the liquefied polyol is obtained by reacting component A, polyethylene glycol 800, glycerol and ammonium sulfate in a mass ratio of (20-40):90:10:(3-5); the component A is selected from one or more of chicken feathers, egg shells and chicken manure; the isocyanate is selected from one or more of hexamethylene diisocyanate, 3-(trifluoromethyl)phenyl isocyanate and 5-isocyanate-2-methylpyridine; The self-repairing modified bio-based coating material with super mechanical properties is prepared by the following method: (1) adding maleimide to 4-hydroxynonenal, stirring continuously at 55-65° C. for 20-40 min, adding p-cresol after the stirring is completed, adjusting the pH to 10 after the reaction is stable, and obtaining a toughening agent after drying; (2) dissolving the second component in anhydrous ethanol, adding the first component, stirring continuously at 30-40° C., adjusting the pH to 9.5-10, stirring for 5-10 minutes, and then ultrasonically oscillating, and drying to obtain a self-healing material; (3) adding the toughening agent to the self-healing material, stirring continuously under the condition of introducing nitrogen, mixing the two evenly, adjusting the pH to 10, and drying to obtain an intermediate product; The intermediate product is added to the coating liquid matrix, and an organic solvent is added to the mixture. After stirring for 3-5 minutes, ultrasonic vibration is performed for 15-25 minutes. After it is uniform, it is taken out and stirred to remove excess organic solvent. When it becomes viscous, stirring is stopped to obtain a self-healing modified bio-based coating material with super mechanical properties.

2. The bio-based coating material with super mechanical properties and self-repairing modification according to claim 1, characterized in that: In step (3), the organic solvent is tetrahydrofuran.

3. Use of the self-repairing modified bio-based coating material with super mechanical properties as claimed in claim 1 or 2 in the preparation of controlled-release fertilizers.

4. A self-repairing coated controlled-release fertilizer, characterized in that: It comprises a fertilizer core, and the super mechanical property self-repairing modified bio-based coating material according to claim 1 or 2 sprayed on the surface of the fertilizer core; the super mechanical property self-repairing modified bio-based coating material accounts for 5-7% of the weight of the fertilizer core.

5. The method for preparing the self-repairing coated controlled-release fertilizer according to claim 4, characterized in that: The following steps are involved: The self-repairing modified bio-based coating material with super mechanical properties is sprayed evenly on the surface of the preheated fertilizer core at a pressure of 0.3-0.5MPa, and cured at 65-75°C for 4-6 minutes.

Citation Information

Patent Citations

  • Bio-based membrane with self-repairing function, coated controlled-release fertilizer and preparation method

    CN113788711A

  • Preparation method for modified biology base polyurethane and application thereof in slow release fertilizer

    CN108864393A

  • Self-assembly and self-repair coated controlled-release fertilizer with loaded functional substances and method for preparing self-assembly and self-repair coated controlled-release fertilizer

    CN109734509A

Cited By

  • Bio-based coated controlled-release fertilizer capable of being rapidly and fully degraded and preparation method of bio-based coated controlled-release fertilizer

    CN120383498A

  • A rapidly biodegradable, fully degradable, bio-based coated controlled-release fertilizer and its preparation method

    CN120383498B